PENGARUH KOMPENSASI DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA BANK TABUNGAN NEGARA CABANG PANAKKUKANG MAKASSAR - Sadariah (Paser Institute Management and Busines, 2023)
This research aims to know the impact of the organization's compensation and climate on the employees' satisfaction at the bank's bank savings branch of Makarksar.The type of data used is qualitative and qualitative data with primary and secondary data suberfuge.The method of analysis used is descriptive and statistical analysis with 60 responders with multiple linear regression calculations, correlation, coefficient determination, T test and f test. The research results show: 1. It has some positive effects and significant compensation to employees work satisfaction 2. The influential organization for positive and significant job satisfaction. employees 3.The organization's compensation and climate impact simultaneously on employees' satisfaction in the bank's bank's bank savings of the Makarksar branch.